Cave-dwelling bats (Mammalia: Chiroptera) and conservation concerns in South central Mindanao, Philippines - Krizler C. Tanalgo; John Aries G. Tabora (Journal of Threatened Taxa, 2015)
The stable microclimate in caves provides a relatively constant habitat for many bat species in the Philippines, but human encroachment continues to disrupt this habitat and imperil many of the species roosting in the caves.  In South central Mindanao, the diversity and conservation status of cave bats remain undocumented and unexplored.  We employed mist-netting to capture bats from five different caves within the town of Kabacan, northern Cotabato, Philippines.  A total of 14 bat species were identified including the Philippine endemics Hipposideros pygmaeus and Ptenochirus jagori and the threatened Megaerops wetmorei. However, despite the declining conservation status of the bats, local disturbance such as bat hunting for bush meat and unregulated tourism are currently taking place in the caves.  Large species such as Eonycteris spelaea and Rousettus amplexicaudatus are killed almost every day for food and trade.  Therefore, the high species richness, and the presence of endemic and threatened species coupled with the occurrence of anthropogenic disturbances in caves suggests the need for an urgent and effective conservation intervention involving the local government and public community.